ChemInform Abstract: Biophysical Studies of the Amyloid β‐Peptide: Interactions with Metal Ions and Small Molecules. Issue 47 (4th November 2013) - Waermlaender, Sebastian; Tiiman, Ann; Abelein, Axel; Luo, Jinghui; Jarvet, Jyri; Soederberg, Kajsa L.; Danielsson, Jens; Graeslund, Astrid
Abstract Review: 145 refs.